UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA PEMBELAJARAN DARING - Eka Putra Wahyu Suminar (Universitas Muhammadiyah Gresik, 2020)
The aim of this study is to increase interest and achievement in mathematics learning of class X AKL 2 SMK Negeri 2 Pacitan after participating in online learning with the Problem Based Learning model. This classroom action research was conducted in 3 cycles, each of which consisted of one meeting. Each cycle consists of four steps, namely planning, acting, observing and reflecting. The results of this study indicate that the percentage of students' interest in learning scores in the pre-cycle was 68% with low qualifications, increased in cycle I by 77% with high qualifications, cycle II by 81% with high qualifications, and cycle III by 83% with high qualifications. Meanwhile, the learning achievement of students showed an average pre-cycle score of 64 with the percentage of students completing learning by 32%, increasing in cycle I by 79 with the percentage of students completing learning by 71%, cycle II of 79 with the percentage of students completing learning by 81%, and cycle III was 81 with the percentage of students completing learning by 90%. Based on the results of this study, it can be concluded that the indicators of success of this study are fulfilled and the application of the Problem Based Learning model in online learning can increase students' interest and learning achievement.